Isolation and Characterization of Probiotic Lactic Acid Bacteria from Traditional Turkish Fermented Foods with in Vitro Safety and Functional Evaluation - Kavak, Akif Emre; Kan, Nagehan; Orsel, Emre Kursat; Caglayan, Irem Nur; Alimoglu, Zerya Beyza (BENTHAM SCIENCE PUBL LTD, 2026)
Introduction: The objectives of the present study were to isolate and identify lactic acid bacteria (LAB) from locally sourced shalgam and traditional Turkish fermented cheese to evaluate their safety and probiotic potential. Materials and Methods: A total of 51 bacterial isolates were obtained from these two sources, and 33 were identified using RAPD PCR and 16S rRNA sequencing. Five of the identified strains were selected for further characterization. Safety assessments included antibiotic susceptibility testing and evaluation of their ability to produce deoxyribonuclease and gelatinase. The probiotic potential was examined using colorectal cell culture models by assessing their ability to adhere to and colonize the intestinal epithelium, as well as their resistance to bile salts and their tolerance to low pH. Results: The antibiotic resistance observed in all strains was determined to be intrinsic, and none of the isolates produced deoxyribonuclease or gelatinase. All five strains showed higher viability at pH 3 compared to pH 2. Furthermore, in gastric juice and simulated intestinal fluid resistance studies, viability rates above 80% were observed. Considering five strains, 0.5% bile salt, viability ranged from 6.67 to 8.00 log10 CFU/mL. 1% bile salts was observed in the range from 2.55 to 8.40 log10 CFU/mL. Discussion: The selected five probiotic strains stood out in terms of probiotic properties compared to other strains. Conclusion These findings suggest their potential as safe, locally derived probiotic candidates for functional food development.
Keywords: Probiotics; microbiota; 16s rRNA; fermented food; cell culture; nuvita biosearch center; ANTIBIOTIC-RESISTANCE; STRAINS; LACTOBACILLI; ADHESION; STARTER; Nutrition & Dietetics